Does food insecurity impact subjective evaluation of well-being? Evidence from a developing country - Wisdom Akpalu; Aaron K. Christian; Samuel Nii Ardey Codjoe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Understanding the relationship between food insecurity and subjective evaluation of well-being is critical in designing social welfare policies, especially in developing countries. Surprisingly, literature on the topic is scarce. This study adopted Van Praag's theoretical framework and used household survey data from Ghana to investigate the monetary income which households facing severe food insecurity require to reach a given level of verbal qualification of well-being. We found that households that are food insecure require a higher monetary income to reach the same level of verbal qualification of well-being than their counterparts who are food secure. Furthermore, per capita household income levels positively correlate with monetary income requirements, indicating a weak correlation between food security and per capita household income. Households that receive support from others require a lower level of income than either those who give support or those who neither give nor receive support.
Keywords: I31; 330; food security; well-being; equivalent scale